1995
DOI: 10.1159/000203966
|View full text |Cite
|
Sign up to set email alerts
|

Production and Expression of Granulocyte- and Macrophage-Colony-Stimulating Factors in Newborns: Their Roles in Leukocytosis at Birth

Abstract: We analyzed the production and expression of three colony-stimulating factors (CSFs) in neonates to clarify the mechanism of leukocytosis at birth. Serial blood samples (n = 23) were collected from mothers, cord blood, and from newborn infants on days 1,5, and 30 after birth. The serum levels of granulo-cyte-CSF (G-CSF), granulocyte/macrophage-CSF (GM-CSF) and macro-phage-CSF (M-CSF) were measured by ELISA. The G-CSF levels on day 1 after birth were significantly higher than those thereafter, and they were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
(28 reference statements)
0
12
0
2
Order By: Relevance
“…These effects have been mainly related to endocrine-metabolic variations, particularly the increased cortisol and catecholamine secretion after stressful delivery, or, to a lesser extent, to anesthetic drugs given to the mother during general anesthesia for cesarean section. The increase of neutrophils after stressful delivery may also be related to the displacement of neutrophils from the marginal layer of vessels, which is known to happen after violent exercise in adults [14], or to variations in the production of hematopoietic growth factors, mainly granulocyte colony stimulating factor and granulocyte-macrophage colony stimulation factor [15].…”
Section: Discussionmentioning
confidence: 99%
“…These effects have been mainly related to endocrine-metabolic variations, particularly the increased cortisol and catecholamine secretion after stressful delivery, or, to a lesser extent, to anesthetic drugs given to the mother during general anesthesia for cesarean section. The increase of neutrophils after stressful delivery may also be related to the displacement of neutrophils from the marginal layer of vessels, which is known to happen after violent exercise in adults [14], or to variations in the production of hematopoietic growth factors, mainly granulocyte colony stimulating factor and granulocyte-macrophage colony stimulation factor [15].…”
Section: Discussionmentioning
confidence: 99%
“…Son olarak püberte döneminde hormonal deği-şimlere bağlı olarak kızlarda menstrüel kan kaybına bağlı demir eksikliğine eğilim erkeklerde ise yük-sek Hb değerleri görülmektedir [26,27]. Riskli gebeliklere ve doğum stresine bağlı olarak annede artan stres hormonların etkisiyle yenidoğan lökositoz ve nötrofiliye eğilimle doğar [29]. Dört ay-4 yaş arasında geçirilen viral enfeksiyonlar ve sık tekrarlanan aşılamaya bağlı aşı yanıtının etkisi nedeniyle fizyolojik lenfositoz izlenir [28,30].…”
Section: Eri̇trosi̇tlerunclassified
“…high concentration of maternal serum M-CSF [9]. Furthermore, it has been reported that low concentrations of serum M-CSF are associated with unexplained recurrent spontaneous abortion in humans [4,14].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, M-CSF concentrations in maternal peripheral blood during the estrous cycle and pregnancy have been reported in humans and mice. In humans, M-CSF concentrations in maternal peripheral blood increase as pregnancy progresses, peak at term and then decrease immediately after parturition until they reach the base level of non-pregnancy [7,9,16,24,28,31,32,34,36]. Ishii et al reported that M-CSF in maternal peripheral blood is produced in the uterus, placenta and peripheral monocytes and that M-CSF of uterine and placental origin is related to a There were no significant differences depending on the stage of the estrous cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation